Boost Students' Writing Competency in Writing Caption on Instagram - Meita Lesmiaty Khasyar (STKIP Muhammadiyah Bogor, 2020)
This article explores the implementation of writing captions on Instagram towards students of SMAN 6 Bogor. According to basic competencies of English subject in Curriculum 2013, one of the competencies that the students of grade XII of SMA are able to compose captions. Instagram is an online mobile photo-sharing, story-sharing, and video-sharing. It is one of the social media tools widely used by teenagers. This study is intended to reports how the implementation of EFL students’ writing competency in using Instagram and whether the learning activity can boost students’ interest and encourage students to write from what they know. Further, the discussion also takes into the issues of the problem that may exist during the application of Instagram as a learning tool and the solution proposed by the teacher to solve the problems will also intensively investigate. Employing a qualitative approach, observation and interview use as the instrument of this present study. The students at SMA 6 Bogor choose as the informant of this study. The students are under the researcher's supervision. Activities are designed in accordance with the course objectives to share information about the students and the phenomenon.